Labetalol Pretreatment Reduces Blood Pressure Instability During Surgical Resection of Pheochromocytoma - Peter Chi-Ho Chung; Yuet-Tong Ng; Jing-Ru Hsieh; Min-Wen Yang; Allen Hon-Lun Li (Journal of the Formosan Medical Association, 2006)
To evaluate the effect of pretreatment with the mixed alpha- and beta-adrenergic blocker, labetalol, on blood pressure instability during surgical resection of pheochromocytoma. Methods: Blood pressure stability and surgical results were compared between patients in the saline (n = 11) and labetalol (n = 15) groups. Anesthesia was induced with fentanyl, sodium thiopental and atracurium, and maintained with isoflurane in a 50% oxygen/nitrous oxide mixture. Intravenous labetalol was administered in the labetalol group before surgical incision, with the maximal dose being 1.2 mg/kg, while normal saline was administered to patients in the control, saline, group. Supplemental intravenous sodium nitroprusside (SNP) infusion was administered whenever systolic blood pressure exceeded 180 mmHg. The number of patients with intraoperative hypertension or hypotension, dosage of SNP administered, number of intraoperative hypertension episodes, use of fluid and blood transfusion, and heart rate (defined as the mean of heart rate every 5 minutes throughout the operation) were compared between these two groups. Results: The number of patients with intraoperative hypertension, number of patients receiving SNP, dose of SNP administered, and number of hypertension episodes were significantly lower in patients who received labetalol pretreatment than in control patients. Conclusion: This study has demonstrated that labetalol pretreatment (1.2 mg/kg) with supplemental SNP provides more favorable blood pressure control during surgical resection of pheochromocytoma than with SNP alone.